Advancing Sustainable Materials: Synthesis and Analysis of Polyurethane Biocomposites from Hydrogenated Safflower Oil - Aydogmus, Ercan; Yanen, Cenk; Kistak, Celal (Mdpi, 2025)
Featured Application The hydrogenated safflower oil-based biocomposites are specifically suited for use in biodegradable packaging materials, offering an eco-friendly solution to reduce plastic waste. Additionally, they can be applied in lightweight automotive components, such as interior panels, where durability and sustainability are critical. Their customizable properties also make them ideal for green building materials, including insulation panels.Abstract The growing demand for sustainable and environmentally friendly materials has highlighted the need for innovative alternatives to traditional plastics and composites. This study explores the development of polyurethane-based biocomposites synthesized using hydrogenated safflower oil (HSO), hydrogen gas, and a nickel catalyst. Safflower oil was hydrogenated via a catalytic hydrogenation mechanism, transforming carbon-carbon double bonds into saturated fatty acids. The process, optimized using response surface methodology (RSM), was conducted at 225 degrees C, 8 atmospheres, and 6 h, achieving a yield of 67%. Hydrogenation improved the physical and chemical properties of the biocomposites. Biocomposites were synthesized by combining HSO with methylene diphenyl diisocyanate (MDI) as a crosslinker. Optimal performance was observed at 2.5% HSO content, enhancing material properties. However, higher HSO content negatively affected biocomposite density and hardness, and surface morphology analyses revealed that increased HSO content led to irregular pore structures. These findings underscore the balance required in material composition to achieve optimal performance. This study presents a novel approach to producing hydrogenation-modified HSO-based biocomposites, providing an eco-friendly and sustainable alternative for industries such as packaging, construction, and automotive applications. The advancements contribute to reducing environmental impact and enhancing the performance of renewable material technologies.
Keywords: hydrogenated safflower oil; polyurethane based-biocomposites; catalytic hydrogenation; sustainable materials